Photoluminescence in Raman Scattering: Effects of HfO2 Template Layer on Ultrananocrystalline Diamond (UNCD) Films Grown on Stainless Steel Substrates - de Obaldia, Elida; Tirado, Pablo; Alcantar, Jesús; Montes, Jorge; Auciello, Orlando (KnE Engineering, 2018)
The growth of polycrystalline diamond films can play an important role in industry if they can be grown on industrially used materials like aluminum (Al) or stainless steel (SS). A critical issue related to the growth of ultrananocrystalline diamond (UNCD) thin films on metals like SS, in a Hydrogen rich environment like the one present during growth of UNCD films, is the diffusion of Hydrogen (H) into the SS substrate, as it has been observed in prior research, which results in hydride formation in the SS that induce brittleness in the SS substrate. Several interface layers have been proposed described to avoid the H diffusion into the SS. However, HfO2 has not been explored. The work reported here was focused on investigating the growth of UNCD films on commercially available SS substrates by using an interface layer of HfO2, which was found to be a good diffusion barrier for H to inhibit penetration into the SS substrate. The samples where characterized with SEM and Raman spectroscopy. A photoluminescence (PL) effect, observed in the Raman scattering analysis, is present in all the samples. The PL effect may be due to the interaction of the UNCD / HfO2 interface. and the SS substrate rather than UNCD film alone. The novel result from the experiments described here, is the fact that it is possible to grow UNCD films on unseeded HfO2 layers on SS substrates. Keywords: Poly-crystalline diamond, photoluminescence, UNCD, Stainless Steel, Hafnium Dioxide